New Discorhabdin Alkaloids from the Antarctic Deep-Sea Sponge Latrunculia biformis - Fengjie Li; Christian Peifer; Dorte Janussen; Deniz Tasdemir (Marine Drugs, 2019)
The sponge genus Latrunculia is a prolific source of discorhabdin type pyrroloiminoquinone alkaloids. In the continuation of our research interest into this genus, we studied the Antarctic deep-sea sponge Latrunculia biformis that showed potent in vitro anticancer activity. A targeted isolation process guided by bioactivity and molecular networking-based metabolomics yielded three known discorhabdins, (−)-discorhabdin L (1), (+)-discorhabdin A (2), (+)-discorhabdin Q (3), and three new discorhabdin analogs (−)-2-bromo-discorhabdin D (4), (−)-1-acetyl-discorhabdin L (5), and (+)-1-octacosatrienoyl-discorhabdin L (6) from the MeOH-soluble portion of the organic extract. The chemical structures of 1–6 were elucidated by extensive NMR, HR-ESIMS, FT-IR, [α]D, and ECD (Electronic Circular Dichroism) spectroscopy analyses. Compounds 1, 5, and 6 showed promising anticancer activity with IC50 values of 0.94, 2.71, and 34.0 µM, respectively. Compounds 1–6 and the enantiomer of 1 ((+)-discorhabdin L, 1e) were docked to the active sites of two anticancer targets, topoisomerase I-II and indoleamine 2,3-dioxygenase (IDO1), to reveal, for the first time, the binding potential of discorhabdins to these proteins. Compounds 5 and 6 are the first discorhabdin analogs with an ester function at C-1 and 6 is the first discorhabdin bearing a long-chain fatty acid at this position. This study confirms Latrunculia sponges to be excellent sources of chemically diverse discorhabdin alkaloids.